The relevance of using economic and mathematical models in risk management of food industry enterprises - Lysenko (Zvyozdochkina), Elena (My University, 2021)
Розглянуто актуальність створення економіко-математичних моделей в умовах невизначеності для дослідження економічних процесів на харчових підприємствах. Встановлено необхідність використання моделювання в умовах ризику з метою прийняття більш обґрунтованого рішення. The relevance of creating economic-mathematical models in conditions of uncertainty for the study of economic processes at food enterprises is considered. The necessity of using modeling in conditions of risk in order to make a more informed decision has been established.
Keywords: менеджмент; економіко-математичні моделі; невизначеність; ризик; прийняття рішення; management; economic and mathematical models; uncertainty; risk; making a decision; кафедра економіки праці та менеджменту